Covid-19 Pandemic and Sustainable Green Product Strategies: The Case Study for Textile Recycle Sector - Bekir Kose; Mesut Atasever (International Journal of Scientific Multidisciplinary Research, 2023)
The concept of recycling, which is one of the most important issues that the whole world has focused on for the last quarter century, has become a business issue that cannot be ignored in terms of businesses. Businesses have come face to face with different reasons such as legal obligations from time to time, and the idea of making more profit by thinking that this is areas that other businesses do not prefer. However, the recycling strategies of businesses in the world seem to be a problem because they are not clear in many respects. The aim of this study is to discuss and interpret the situation and differences of business strategies on recycling before and after the covid-19 pandemic and the innovations that the covid-19 pandemic crisis has brought to this field. For this purpose, the information obtained by applying the method of interviewing with the recycling operators was subjected to content analysis. The study is important because it is an original study on the subject of recycling, which opens a different window in the increasingly polluted world with industrialization. It is expected that this study will guide and be beneficial to businesses related to recycling and academics studing in this field